Determinants of high-risk coronary artery disease in ostensibly healthy male master endurance athletes. (14th October 2021) - Parry-Williams, G; Obaid, D; Miles, C; Basu, J; MacLachlan, H; Moser, J; Vlahos, I; O'Driscoll, J; Chis Ster, I; Papadakis, M; Tome Esteban, M T; Sharma, S
Abstract: Background: Healthy male master endurance athletes have a greater prevalence of high coronary calcium (CAC) scores compared to healthy sedentary counterparts, and some demonstrate high-risk plaque features. A number of theories have been postulated but reasons remain unclear. Concurrently atherosclerotic coronary artery disease (CAD) is the most common cause of sudden cardiac death in male master athletes drawing much public and scientific interest and making this an important public health issue. Purpose: To examine the relationship of age, resting systolic blood pressure (SBP), exercise dose and sporting discipline with high-risk CAD markers in male master endurance athletes. Methods: A prospective study undertaken over 19 months evaluated 214 male master (40–65 years) endurance athletes, free from known cardiovascular risk factors, symptoms or relevant health conditions. Clinical evaluation included cardiopulmonary exercise test, resting blood pressure (BP) and coronary computed tomogram angiography (CCTA). CCTA assessed CAC score, significant stenosis, (>50%) and plaque vulnerability markers. Exercise dose was defined by years of endurance exercise and average MET-hours/week (lifetime exercise volume multiplied by the metabolic equivalent scores). Resting BP was the average of 3 consecutive supine measures after at least 5 minutes rest. Results: Athletes (mean age 51, SD 70.1) exercised for minimum 6 hours/week (median 8.5) for a median of 15 years (2–26). Almost half (60.2%) were multi-endurance athletes i.e. any combination swimming, cycling and running. The remainder were runners (22.4%) and cyclists (15.4%). Median Framingham risk score 3.2% (1.8–5.8). The mean resting BP was 129/80 mmHg and a quarter (26%) of athletes were hypertensive (≥140/90 mmHg) at rest. A CAC score >100 Agatston units (AU) was present in 16% of athletes. There was a total of 15 stenotic lesions in 11 (5%) athletes. 13% had plaque vulnerability markers. Logistic regression evaluated whether age, resting SBP, exercise dose measures and sporting discipline were predictive for a CAC score >100 AU, significant stenosis and plaque vulnerability markers (table 1). CAC score was associated with age, years of endurance exercise and resting SBP. A Stenosis >50% and plaque vulnerability markers were associated with resting SBP and cycling compared with all other sporting disciplines. Conclusion: Despite correcting for age, higher exercise dose (years endurance exercise) is associated with CAC score >100 AU but does not predict significant stenosis or plaque vulnerability markers. Resting SBP and cycling strongly predict high-risk disease. Cycling enables a greater intensity of exercise compared with other endurance sports, which may be associated with prolonged rises in SBP. Resting SBP and cycling are important determinants for high-risk CAD in middle-aged male endurance athletes and should be considered when risk stratifying in pre-participation evaluation. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship